(3GdagQSJs - (3GHf GdfOje , eMeO Hf ESMGb Hf eMeO Hf ESMGb , CHh GdaQL Hf CHj jYbhH GdfOje,J (B438 (3g` s
(3ChdgG (B:s
(3gPG agQSJ cJH GdYdhe GdbOjeI ef JUGfja GdjhfGf hGdaQS hGdgfO GdehLhO efgG HdZI GdYQH hgh GQHYI ebGdGJ GdebGdI GdChdi CQHYI afhf s
(3BNQgG (B:s
(3cJGH GdCeGd Ydi QCS GdchQ bGd eMeO Hf ESMGb hGdcJH GdeDda ai gPG GdTCf CcKQ hCYXe ef Cf JMUi JeJ GdebGdI GdYGTQI ef cJGH GdagQSJ hHJeGegG Je LejY GdcJGH hddg GdMeO hGdefg hGdMhd hGdbhI hUdi Gdgd Ydi SjOfG eMeO hYdi Bdg hSde JSdjekG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B29 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B41s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3agGQS hecJHGJ (B/ (3ecJHI chHQdi (B(1134) s
Keywords: (3GdJGQjNs